How to treat mania. (3rd August 2020) - Pacchiarotti, I.; Anmella, G.; Colomer, L.; Vieta, E.
Abstract : Objective: In this paper, we aimed at reviewing evidence‐based treatment options for bipolar mania and proposed tentative evidence‐based clinical suggestions regarding the management of a manic episode, especially regarding the choice of the proper mood stabilizer and antipsychotic medication. Method: A narrative review was undertaken addressing 'treatment of bipolar mania'. Findings have been synthesized and incorporated with clinical experience into a model to support different treatment choices. Results: To date, there is solid evidence supporting the use of several medications, such as lithium, divalproex, and carbamazepine, and antipsychotics, such as chlorpromazine, haloperidol, risperidone, olanzapine, quetiapine, ziprasidone, aripiprazole, inhaled loxapine, asenapine, and cariprazine in acute mania, and some evidence supporting the use of clozapine or electroconvulsive therapy in treatment‐refractory cases. However, in clinical practice, when making decisions about treatment, personalized treatment is needed, according to the different clinical presentations and more complex clinical situations within the manic episode and considering a long‐term view and with the objective of not only a symptomatic but also functional recovery. After remission from acute mania, psychoeducation strategies are useful to ensure adherence. Discussion: Despite the evidence forefficacy of many currently available treatments for mania, the majority of RCTs provide little direction for the clinician as to what steps might be optimal in different presentations of mania as well as in the presence of specific patient characteristics. Manic episodes should be managed on a personalized basis considering the clinical course and patient criteria and with the expectation of maintaining that treatment in the long‐term.